A double-edged sword: the merits and the policy implications of Google Translate in higher education - Mundt, Klaus; Groves, Michael J. (Taylor & Francis, 2016)
Machine translation, specifically Google Translate is freely available on a number of devices, and is improving in its ability to provide grammatically accurate translations. This development has the potential to provoke a major transformation in the internationalisation process at universities, since students may be, in the future, able to use technology to circumvent traditional language learning processes. While this is a potentially empowering move that may facilitate academic exchange and the diversification of the learner and researcher community at an international level, it is also a potentially problematic issue in two main respects. Firstly, the technology is at present unable to align to the socio-linguistic aspects of university level writing and may be misunderstood as a remedy to lack of writer language proficiency – a role it is not able to fulfil. Secondly, it introduces a new dimension to the production of academic work that may clash with Higher Education policy and, thus, requires legislation, in particular in light issues such as plagiarism and academic misconduct. This paper considers these issues against the background of English as a Global Lingua Franca, and argues two points. First of these is that HEIs need to develop an understanding and code of practice for the use of this technology. Secondly, three strands of potential future research will be presented